Development of multifunctional cassava starch-based edible coating for pork and chicken meats stored at ambient temperatures - Manalo, Monica R.; Gabriel, Alonzo A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
Abstract
Thesis (M.S. Food Science)--University of the Philippines Diliman
Keywords: Edible coatings -- Philippines; Meat -- Microbiology -- Philippines; Meat -- Packaging -- Philippines; Food -- Packaging -- Philippines